Variação radial e longitudinal da densidade aparente e estimativa de massa de Toona ciliata - Silva, Tatiane Antunes da (2015)
Australian Cedar (Toona ciliata), belongs to the Meliaceae family and has been cultivated in many Brazilian sites. When compared to natural forest species it has fast growth and has been used as an option to substitute native woods, such as mahogany (Swietenia macrophylla) and cedar (Cedrella odorata). The main purpose of this work was to evaluate the variation in apparent density and propose a model for stem mass estimation this study used trees with 52 months old, from plantation areas, in Campo Belo county, Minas Gerais state, Brazil. Two distinct progenies were chosen and had wood discs removed in the following positions from the tree base: 0.15 m, 0.70 m, 1.30 m and 30%, 50%, 70% and 85% of the total height. Wood samples from the disks were collected in order to conduct X-ray densitometry. The X-ray densitometry allowed us to know density variation from pit to bark and from base to top of trees. The density increases from pit to bark. From base to top of the tree, the density decreases up to DBH position and, after that, increases until the top of the tree. The estimated value for mean apparent density was 0.422 g/cm³. Based on the longitudinal variation of apparent density it was possible to propose a model for mass estimation. The model, which considers the estimated apparent density, was used to estimate the total mass (ton/ha). The total mass estimated by the model (53.1 ton/ha) was greater than that estimated using DBH wood density values (50.9 ton/ha).